Determent Total Factor Productivity in Palestinian - & Bader Hamdan; Sameer Abu-Mudallalah (My University, 2013)
This study aimed to examine and analyse the Determinant total factor productivity in Palestine. The researcher used econometrics model which is compatible with the privacy of the Palestinian economy, in order to determine the contribution of production factors in economic growth as a first step. Moreover, the study aimed to analyze the determinants and the factors affecting the growth of total factor productivity (TFP) during the period (1996-2010). To achieve this goal the researcher used time series analysis method. The results have shown that economic variables contain the root of unity, which is unstable over time. However, it became stable after first differences. The researcher subjected the variables to Johansson integration test, which proved the existence of two bounds of integration between the variables of the study. The study found number of results, including:the importance of the effect of real effective exchange rate, direct credit facilities, economic openness, inflation, and foreign direct investment. The contribution of these factors was significant and consistent with the economic theory. Both inflation, and direct credit facilities, statistically was not significant. However, inflation effect was consistent with the economic theory in this area. While, in contrast, the contribution of direct credit facilities is inconsistent with the economic theory. The study recommended to focus on strengthening positive factors affecting the growth of the overall productivity of the factors of production: fetching foreign direct investment and enhancing the role of exports Also, banks are required to specify a great deal of direct credit facilities volume of productivity sectors.

هدفت الدراسة إلى دراسة وتحليل محددات الانتاجية الكلية لعوامل الإنتاج في فلسطين خلال الفترة (1996-2010)، وذلك باستخدام نموذج قياسي يتوافق وخصوصية الاقتصاد الفلسطيني، من أجل تحديد وقياس مساهمة محددات الإنتاجية الكلية لعوامل الإنتاج، وقد تم استخدام أسلوب تحليل السلاسل الزمنية. وقد أوضحت النتائج القياسية على احتواء المتغيرات الاقتصادية على جذر الوحدة، أي أنها غير مستقرة عبر الزمن، وتصبح المتغيرات مستقرة بعد الفروق الأولى، وأعقب ذلك إخضاع المتغيرات لاختبار التكامل المشترك بطريقة جوهانسون، والتي أثبتت وجود متجهين للتكامل المشترك بين متغيرات الدراسة.  وقد توصلت الدراسة إلى جملة من النتائج منها: أهمية تأثير كل من (التضخم، والتسهيلات الائتمانية المباشرة، والانفتاح الاقتصادي، والاستثمار الأجنبي المباشر، وسعر الصرف الحقيقي الفعال)، حيث كانت مساهمة هذه العوامل معنوية ومتسقة مع النظرية الاقتصادية، بينما كان كل من: التضخم، والتسهيلات الائتمانية المباشرة، غير معنوي إحصائياً، ورغم ذلك جاءت إشارة التضخم متفقة مع النظرية الاقتصادية في هذا المجال، بينما كانت مساهمة التسهيلات الائتمانية المباشرة غير متسقة مع النظرية الاقتصادية. واستناداً إلى نتائج الدراسة فقد أوصت الدراسة التركيز على تعزيز العوامل المؤثرة إيجابياً في نمو الإنتاجية الكلية لعوامل الإنتاج: كجلب الاستثمار الأجنبي المباشر وتعزيز دور الصادرات. وإلزام المصارف العاملة في الأراضي الفلسطينية بتخصيص الجزء الأكبر من حجم التسهيلات الائتمانية المباشرة للقطاعات الإنتاجية، والتي بحاجة لموارد مالية.
محددات الانتاجية الكلية لعوامل الإنتاج في فلسطين